The impact of child work on cognitive development: Results from four low to middle income countries - Michael P. Keane; Sonya Krutikova; Timothy Neal (Institute for Fiscal Studies (IFS), 2018)
We study the relationship between child work and cognitive development in four Low and Middle Income Countries. We address a key weakness in the literature by including children's full time-use vector in the analysis, which leads to different findings from previous studies which do not distinguish between alternative counter-factual activities. We find child work is only detrimental if it crowds out school/study time rather than leisure. Furthermore, the marginal effects of substituting domestic chores or economic activities for school/study time are similar. Thus, policies to enhance child development should target a shift from all forms of work toward educational activities.
Keywords: I25; J13; J24; O15; 330; Child labour; Child development; Education; Time use; Item response theory; Value added models